2010
DOI: 10.3109/02656736.2010.493915
|View full text |Cite
|
Sign up to set email alerts
|

Present and future technology for simultaneous superficial thermoradiotherapy of breast cancer

Abstract: This paper reviews systems and techniques to deliver simultaneous thermoradiotherapy of breast cancer. It first covers the clinical implementation of simultaneous delivery of superficial (microwave or ultrasound) hyperthermia and external photon beam radiotherapy, first using a Co-60 teletherapy unit and later medical linear accelerators. The parallel development and related studies of the SURLAS, an advanced system specifically designed and developed for simultaneous thermoradiotherapy, follows. The performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 75 publications
(76 reference statements)
0
22
0
Order By: Relevance
“…[27,28]). Preclinical and clinical studies showed a much better effect of combined RT/HT with simultaneous application [8,9,29], achieving a thermal enhancement ratio (TER) from . Mean temperature profiles within tissues during wIRA-exposure under steady state conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[27,28]). Preclinical and clinical studies showed a much better effect of combined RT/HT with simultaneous application [8,9,29], achieving a thermal enhancement ratio (TER) from . Mean temperature profiles within tissues during wIRA-exposure under steady state conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Because the effect of HT is no longer tumour selective when given simultaneously with RT, an increase in therapeutic ratio can only be obtained when the volume where RT and HT are given simultaneously can be geometrically restricted to the macroscopic tumour itself. Superficial and intracavitary HT equipment suitable for simultaneous RT + HT has become available [69][70][71][72] and is clinically applied [73], but such a good delineation is challenging for HT at deep-seated tumour locations as heating in normal tissue in the vicinity of the heated tumour region cannot be avoided due to heat conduction and blood flow, even when well-controlled high resolution HT techniques are used. The tumour delineation must therefore come primarily from RT and image-guided radiotherapy techniques which permit a very precise dose control and TRTP could be used to devise an optimal combination of RT and HT treatment plans achieving high TER in tumour tissue while keeping TER in normal tissue low, even when RT and HT are given simultaneously.…”
Section: Future Prospects and Perspectivementioning
confidence: 99%
“…Hyperthermia has been used to enhance successfully the effects of radiation (2) and is currently being pursued for liposomalmediated drug delivery (10), simultaneous thermal treatment with radiation (11), and MRI guidance for higher-powered thermal ablation (12). It has demonstrated excellent clinical results (13).…”
mentioning
confidence: 99%